Kesetaraan Gender dalam Industri Tembakau: Analisis Pembagian Kerja pada Buruh Tani Tembakau di Pulau Lombok - Rosiana Sri Wulandari; Subaidi, Subaidi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Gender equality in the agricultural sector, especially in tobacco farming, is an important issue affects tha sustainability of the rural economy. This study aims to gain an understanding of how the division of labour is based on gender, including the social, cultural, and economic dynamics thah influence the division of labour. This research uses a descriptive qualitative approach using primary data sources obtained directly from interviews, observations, and focus group discussions (FGDs); and secondary data sources include supporting data in the form of previous research reports and relevant literature. The data analysis technique used in this research is inductive analysis, by analyzing facts or things that are specific or concrete events then generate a conclusion. The results of this study show that the division of labor in tobacco businesses in Lombok reflects a combination of biological (nature) and socio-cultural (nurture) factors. Men generally take on heavy work such as menaek and maintaining the oven fire, while women take on light tasks that require precision, such as begelantang and sorting dry leaves. Social norms put men in charge and women in charge, but both play an important role in maintaining the quality and sustainability of production. Despite wage differentials, women's contributions remain crucial to the success of the business